Pengaruh Website Unsika Terhadap Pemenuhan Informasi Mahasiswa Baru Program Studi S1 Ilmu Komunikasi - Andri Irawan (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
Effect of Using the Unsika Website on Fulfillment of New Student Information Among Communication Studies Students Class of 2019,2020 Universitas Singaperbangsa Karawang). This research was motivated by many complaints related to the incomplete delivery of information to new students in 2018 from the beginning of registration until the lecture had taken place. The author suspects that the information media used by UNSIKA in fulfilling information for new students is not optimal. The purpose of this study is to determine whether there is an effect of using the Unsika website on the fulfillment of information needs. This research method uses quantitative methods using simple regression analysis with the support of Uses and Gratification Theory. The population in this study were students of communication science class 2019, 2020. Sampling technique with probability sampling with a total sample of 79 respondents. Data collection techniques through questionnaires. The results of this study found that: There is a significant influence between the effect of using the Unsika website on the fulfillment of information needs. This is evidenced by the results of simple regression analysis with a significance value of 0.000 <0.05, meaning that the use of the Unsika website has an effect on meeting the information needs of new students with the regression equation Y = 7.722 + 0.213, it can be concluded that the use of the Unsika website is positively related to the fulfillment of student information. new with a high degree of correlation. Keywords: use of the UNSIKA website, fulfillment of information, students of the communication science study program